An innovated HRM framework for sustainability: Multiple case studies in Bangladesh - Andalib, Tarnima Warda; Mohd Ridzuan, Darun; Hasliza, Abdul Halim; Sultana, Umme Salma (Future Academy, 2018)
In this study researchers have innovated a novel HRM framework by focusing on the Bangladeshi listed and large-scale manufacturing organisations. To execute the smooth HRM processes, these organizations have developed their distinctly customized HRM policies and practices those contain necessary HRM perspectives and themes. Nevertheless, in this study two new perspectives regarding managing grievances management system and employees’ rights standards have been addressed and mapped in this framework with each other. Bangladesh Govt. has declared an isolated regulation naming the Bangladesh Labour Act 2006 for all the Bangladeshi listed organizations, where various sections and provisions are included and highlighted regarding employee rights and employees’ grievance management. Nevertheless, researchers applied multiple case studies method in twelve companies and took in-depth interviews to analyze and map these two perspectives in the HRM framework for sustainability. Collected data have been organized and analyzed by using NVIVO Mac and the connections between the themes are developed by using Amos on high level. Findings revealed that perspective named ‘employees’ rights’ has three themes named UDHR, ILO and BDL and the other perspective named ‘grievance management system’ has three themes also named ‘Turnover’, ‘Absenteeism’ and ‘Visible expression of grievances’